2014
DOI: 10.1021/mp500236y
|View full text |Cite
|
Sign up to set email alerts
|

[18F](2S,4S)-4-(3-Fluoropropyl)glutamine as a Tumor Imaging Agent

Abstract: Although the growth and proliferation of most tumors is fueled by glucose, some tumors are more likely to metabolize glutamine. In particular, tumor cells with the upregulated c-Myc gene are generally reprogrammed to utilize glutamine. We have developed new 3-fluoropropyl analogs of glutamine, namely [18F](2S,4R)- and [18F](2S,4S)-4-(3-fluoropropyl)glutamine, 3 and 4, to be used as probes for studying glutamine metabolism in these tumor cells. Optically pure isomers labeled with 18F and 19F (2S,4S) and (2S,4R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Moreover, it was shown that [ 18 F](2 S ,4 R )-4-FGln is metabolized in vivo in part to [ 18 F](2 S ,4 R )-4-FGlu and to 18 F − in both tumor types [16]. In other experiments it was shown that uptake of [ 18 F]FP-Gln by amino acid transporters into 9L tumor cells in F344 9L rats was even more effective than that noted with L-[ 3 H]Gln [19]. The results of a dual labeling experiment with L-[ 3 H]Gln and [ 18 F]FP-Gln showed that the label associated with administered L-[ 3 H]Gln was largely incorporated into macromolecules in 9L tumor cells, whereas label associated with [ 18 F]FP-Gln was not appreciably incorporated into macromolecules [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was shown that [ 18 F](2 S ,4 R )-4-FGln is metabolized in vivo in part to [ 18 F](2 S ,4 R )-4-FGlu and to 18 F − in both tumor types [16]. In other experiments it was shown that uptake of [ 18 F]FP-Gln by amino acid transporters into 9L tumor cells in F344 9L rats was even more effective than that noted with L-[ 3 H]Gln [19]. The results of a dual labeling experiment with L-[ 3 H]Gln and [ 18 F]FP-Gln showed that the label associated with administered L-[ 3 H]Gln was largely incorporated into macromolecules in 9L tumor cells, whereas label associated with [ 18 F]FP-Gln was not appreciably incorporated into macromolecules [19].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the glutamine analogue [ 18 F](2 S ,4 S )-4-(3-fluoropropyl)glutamine ([ 18 F]FP-Gln) was synthesized as a tumor PET imaging agent [19]. This compound is unlikely to undergo defluorination in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…New PET tracers that probe emerging aspects of cancer metabolism are being developed, and some are already used in clinical studies or practice. These tracers, which include 18 F-glutamine, 18 F-glutamate, and 11 C-acetate 8086 , are designed to detect tumours in which 18 FDG uptake is non-diagnostic because the tumour displays relatively little glucose uptake or is in the vicinity of a glucose-avid organ like the brain.…”
Section: Efforts To Understand Cancer Metabolism In Intact Biologicalmentioning
confidence: 99%
“…This tracer was prepared and characterized in cells and rodent tumor models by PET, and indicated the need for a radiotracer with a longer half-life for in vivo imaging, resulting in a number of 18 F-labeled analogues that have now been designed. 203205 …”
Section: [11c]hcn Cyanationmentioning
confidence: 99%